Zrównoważony rozwój i bezpieczeństwo w obrębie ryzyka ekologicznego = Sustainable development and safety of the environmental risk - Zielonka, Robert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sustainable development has not a clear definition and is understood in different ways, although most of it refers to the environment. It seems essential to use natural resources so that economic progress can follow and at the same time little damage to the natural environment could be done. Development for human well-being is necessary, but we must remember it should also be sustainable, although the process is not easy.
Keywords: zrównoważony rozwój; ochrona środowiska; sustainable development; environment protection